Unwanted loneliness among older adults in rural areas: associated factors and guidelines for community intervention - Yurrebaso, A.; Picado-Valverde, E.; García-Valverde, E.; Guzmán-Ordaz, R. (Frontiers in Aging, 2026)
BackgroundUnwanted loneliness among older adults has become a growing public health concern, particularly in rural contexts characterized by population aging, depopulation, and limited access to services. While many interventions focus on functional and social dimensions, the subjective and emotional roots of loneliness remain insufficiently explored. This study aims to identify profiles at greater risk of loneliness and to analyze personal and community activities that may help mitigate it in highly depopulated rural municipalities.MethodsA cross-sectional quantitative study was conducted in five rural areas of western Salamanca, in municipalities with fewer than 500 inhabitants. A total of 153 individuals aged 60 and over participated. Structured interviews were carried out, including a sociodemographic questionnaire, variables related to available services, personal and community activities, and the UCLA Loneliness Scale Version 3. Data was analyzed using descriptive statistics and chi-square tests.Results41.2% of participants reported moderate or severe levels of loneliness. Living alone, having a low educational level, and not engaging in social or leisure activities were associated with higher levels of loneliness. Significant associations were found between loneliness and variables such as living alone (p = 0.012), not talking on the phone (p = 0.024), not reading (p = 0.010), and not engaging in community activities like going out, spending time with family, or exercising (p < 0.01). The availability of services in the municipality showed no statistically significant relationship.ConclusionIn rural contexts, loneliness among older adults appears to be more strongly influenced by the quality and frequency of social relationships than by the mere availability of services. Interventions should address not only structural or functional needs but also the emotional and relational dimensions, through personalized and community-based strategies that promote overall wellbeing. It is crucial to distinguish between social isolation and subjective loneliness, and to guide policies toward the strengthening of human connection.